Etnosains dalam Pembelajaran IPA sebagai Implementasi Kebijakan Kurikulum Merdeka: Suatu Systematic Literature Review - Heni Yunilda Hasibuan; Encep Syarifudin; Suherman; Cecep Anwar Hadi Firdos Santosa (Postgraduate, University of Mataram, 2023)
The Kurikulum Merdeka policy has been implemented extensively in Indonesia since 2022, with one of its focuses being the integration of culture in teaching and learning. Several studies have been conducted on the integration of ethnosciences in science education. However, so far, there have been very few studies that attempt to review the results of the analysis of these articles. Therefore, this study aims to analyze a number of articles related to research on the topic of ethnosciences in science education as an implementation of the Kurikulum Merdeka policy, in order to classify them based on predetermined categories. This study utilizes the systematic literature review (SLR) method, which includes the stages of data search and article collection, article screening, assessment of the quality and suitability of scientific articles, and analysis and data classification. Based on these stages, six scientific articles were obtained, published in six SINTA-accredited journals with a focus on education and published between 2022 and 2023. The results of the quality assessment indicate that four out of the six articles meet the criteria for suitability. Thus, these articles can be considered as sources of information related to research on the topic of ethnosciences in science education as an implementation of the Kurikulum Merdeka policy. The classification has been conducted based on Indonesian culture integrated into science education, educational levels, subjects, and forms of integration of ethnosciences in science education.